Pengaruh Kondisi Sosial Ekonomi Keluarga, Prestasi Belajar, dan Kesempatan Kerja Terhadap Minat Melanjutkan Pendidikan ke Program Magister Fakultas Ekonomi UNP - Sonny Taufik; Tri Kurniawati (Universitas Negeri Padang, 2020)
This study aims to analyze: 1) the effect of family socio-economic conditions on student achievement in the Faculty of Economic UNP. 2) the effect of family socio-economic conditions, student achievement, work opportunities on the interest in continuing education to the Faculty of Economic UNP Masters Program. The type of research is associative descriptive research. The sampling technique used is proportional random sampling, with 79 samples. The data analysis technique used in this study is a descriptive analysisand path analysis. The results show that (1) Family socio-economic conditions has a positive and significant effect on student achievement, (2) Family socio-economic conditions has no significant effect on interest in continuing education to the master's program, (3) Student achievement has a significant effect on interest in continuing education to the master program, (4) Job opportunities has a significant effect on the interest in continuing education to the master program, (5) family socio-economic conditions has indirect effect on the interest in continuing master program through student achievment. Keywords: family socio-economic condition, student achievement, employment oppurtunity, interest in continuing education to the master program